PENYALAHGUNAAN FUNGSI MARKETPLACE DIGITAL SHOPEE “KEY LOGISTIC SHOP” DALAM MENGOMUNIKASIKAN PRODUK PALSU MAYBELLINE TERHADAP KEPUASAN PELANGGAN - Jacob, Delicia Regina; Ardanari, Ilona Amadea; Prajnadi, Prajnadi (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2023)
Due to the increase knowledge in technology, affects the public to distribute and be able to obtained information better. Everyone could freely use media to communicate unlimited things, such as product that they would like to bargain to their buyer. But, not infrequently, there are many person who use this unlimited chance by cheating, such as selling fake big brand products, don’t take responsibility for their negligence intentionally or unintentionally, only pay attention to the quantity of purchase amount, and indifferent to customer complaints. Marketplace should have become a place to disseminating honest information and customer have the right to get a satisfactory transaction. But in our observation with one shop in Shopee, which is Key Logistic Shop, we found the big brand beauty product, Maybelline, is faked and sold until disappoints many customers due to the bad quality and irresponsible seller.